Gamma activity concentration from building materials: Estimation of gamma absorption and indoor radon concentration in Katsina State, Nigeria - Nura Gambo; Ramzun Maizan Ramli; Nurul Zahirah Noor Azman (PLoS ONE, 2025)
In this research, nineteen (19) samples were collected and analyzed with the following objectives: to evaluate the activity concentration of radionuclides, assess gamma absorption, determine indoor radon concentration, and evaluate the public health impact of building materials used in Katsina State, Nigeria. The study aimed to provide critical data that would inform safe construction practices and regulatory compliance. Samples were sourced locally from various quarry sites, while materials such as cement, paint, tiles, and ceiling materials were purchased from local markets. The methodology involved measuring radionuclide activity concentrations using gamma-ray spectroscopy with a Thallium-doped Sodium Iodide (NaI (Tl)) detector, a highly sensitive method suitable for detecting gamma emissions from radionuclides. Radon gas was identified as the primary radiation source. Results revealed varying activity concentrations of radionuclides across different building materials. Most samples, except for Gravel, Brown Clay (Zone A and C), Kaolin, and Fired Clay Bricks, were below the recommended limits for radionuclide. Similarly, for , except for Cement and Thatch, samples were generally below the average value of 35 Bq/kg. However, several samples including Gravel, Paint, Brown Clay (Zones A, B, C), Thatch, Mud Clay, Laterite, Neem tree, Limestone, Fired Clay Bricks, and Gypsum exceeded the average value of 30 Bq/kg for . The overall average activity concentrations across samples were : 232.421, : 11.791, and : 51.1858 all in Bq/kg. The average Radium equivalent and Gamma index was 113.8 Bq/kg and 0.22, respectively, with an alpha index of 0.11. The external and internal hazard indexes averaged 0.2292 and 0.3102, indicating that these materials pose no significant radiological health risk when used in construction, as all values are below international guidelines of 370 Bq/kg and 1 mSv/y. This study concludes with a recommendation for public awareness on the effects of radiation and the need for continued monitoring and regulation of radiation exposure. The significance of this study lies in its contribution to public health and safety, supporting regulatory compliance and helping to prevent potential health risks associated with construction materials.